Animal biodiversity: An introduction to higher-level classification and taxonomic richness - Zhang, Zhi-Qiang (Zootaxa, 2011)
For the kingdom Animalia, 1,552,319 species have been described in 40 phyla in a new evolutionary classification. Among these, the phylum Arthropoda alone represents 1,242,040 species, or about 80% of the total. The most successful group, the Insecta (1,020,007 species), accounts for about 66% of all animals. The most successful insect order, Coleoptera (387,100 species), represents about 38% of all species in 39 insect orders. Another major group in Arthropoda is the class Arachnida (112,201 species), which is dominated by the mites and ticks (Acari 54,617 species) and spiders (43,579 species). Other highly diverse arthropod groups include Crustacea (66,914 species), Trilobitomorpha (19,606 species) and Myriapoda (11,885 species). The phylum Mollusca (117,358 species) is more diverse than other successful invertebrate phyla Platyhelminthes (29,285 species), Nematoda (24,783 species), Echinodermata (20,509 species), Annelida (17,210 species) and Bryozoa (10,941 species). The phylum Craniata, including the vertebrates, represents 64,832 species (for Recent taxa, except for amphibians): among these 7,694 described species of amphibians, 31,958 species of “fish” and 5,750 species of mammals.